Facultative heterochromatin formation in rDNA is essential for cell survival during nutritional starvation. Issue 7 (28th March 2022) - Hirai, Hayato; Takemata, Naomichi; Tamura, Miki; Ohta, Kunihiro
Abstract: During the cellular adaptation to nutrient starvation, cells temporarily decelerate translation processes including ribosomal biogenesis. However, the mechanisms repressing robust gene expression from the ribosomal gene cluster (rDNA) are unclear. Here, we demonstrate that fission yeast cells facing glucose starvation assemble facultative heterochromatin in rDNA leading to its transcriptional repression. Glucose starvation induces quick dissociation of the ATF/CREB-family protein Atf1 from rDNA, where in turn the histone chaperone FACT is recruited to promote H3K9 methylation and heterochromatinization. We also identify the histone acetyltransferase Gcn5 as a repressor of rDNA heterochromatinization in glucose-rich conditions, and this protein dissociates from rDNA upon glucose starvation. Facultative heterochromatin formation in rDNA requires histone deacetylases Clr3 and both the RNAi-dependent and -independent gene silencing pathways. This is essential in adaptation to starvation since mutants lacking heterochromatin formation in rDNA lead to untimely cell death during glucose starvation.